Exclusive Breastfeeding as a Risk Factor for Stunting Among Under-Fives in Urban and Rural Indonesia: A Systematic Review - Wibowo, Rena Anjeli; Rustiawan, Asep (Universitas Ahmad Dahlan, 2025)
Background: Previous research found that children in rural areas have a 1.3 times greater risk of stunting than children in urban areas. Exclusive breastfeeding is one of the risk factors for stunting. The 2017 Indonesian Demographic and Health Survey (IDHS) showed that the percentage of exclusive breastfeeding in urban areas was 37.8%, while in rural areas, it was 46.9%. The purpose of this study was to determine the magnitude of the risk of stunting in toddlers who are not exclusively breastfed in rural and urban areas. Method: This research used a Meta-Analysis Systematic Review by searching articles in PubMed, Google Scholar, and Garuda that were in Indonesian or English and published between 2019 and 2024. Keywords included stunting, risk factors, exclusive breastfeeding, children under five, rural, and urban. The article search used the PICO framework, while the article quality assessment used the Joanna Bright Institute (JBI) Critical Appraisal Instrument. The data collected was presented in a PRISMA diagram and analyzed based on Forest Plot graphs using RevMan 5.4.1. Results: A total of 3,269 articles were identified, and 11 met the criteria. The analysis showed that toddlers not exclusively breastfed had a 3.84 times greater risk of stunting in rural areas and 2.38 times greater for urban regions than exclusively breastfed toddlers. Conclusion: Children who are not exclusively breastfed in rural areas are at greater risk of stunting than those in urban areas.